Novel oral anticoagulants for treatment of deep venous thrombosis and pulmonary embolism (Eurasian Research Bulletin, 2021)
This study is a review-based research paper that involved the review of previously published researches. This study explores understandings about the utilization of oral anticoagulation in the treatment of deep venous thrombosis and pulmonary embolism. PE and DVT are included in the chief significant appearances of VTE (venous thromboembolism), which is included in the three chief general life-aggressive cardiovascular disorders.